2018
DOI: 10.1016/j.ijfatigue.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the fatigue resistance of epoxy nanocomposites by aligning graphene nanoplatelets

Abstract: Graphene nanoplatelets (GNPs) offer great potential for enhancing the multifunctional properties of epoxy polymers, including the cyclic-fatigue crack growth resistance. In the present work we investigate the effectiveness of electric-field alignment of GNPs in increasing the fatigue resistance of such epoxy nanocomposites. The GNPs were aligned in an uncured (liquid) epoxy resin by applying an alternating-current electric field during the curing process, before gelation of the epoxy. The fatigue properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Bhasin et al . [23] have dispersed, using a three-roll mill, GNPs in an epoxy resin which was cured at room temperature using an amine hardener. The epoxy polymers possessed a glass transition temperature of about 90°C.…”
Section: Resultsmentioning
confidence: 99%
“…Bhasin et al . [23] have dispersed, using a three-roll mill, GNPs in an epoxy resin which was cured at room temperature using an amine hardener. The epoxy polymers possessed a glass transition temperature of about 90°C.…”
Section: Resultsmentioning
confidence: 99%
“…These nanofillers drew attention due to their flexible properties, allowing us to create multi-functional composite materials that can be used for a range of applications such as aerospace, energy storage, and electromagnetic interference shielding [ 1 , 2 , 3 ]. Two-dimensional nanomaterials such as graphene, due to their high aspect ratio (AR), offer increased fatigue resistance and fracture toughness through deflection of crack propagation and bridging mechanics [ 4 , 5 , 6 ]. However, such fillers are hydrophobic and do not form bonds with polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have studied fatigue life of epoxy nanocomposites which mostly incorporate CNTs (e.g., [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]) and rarely rGO [ 16 ] and GNPs [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Rafael et al [ 24 ] appeared to be the first researchers studying the effect of graphene nanoparticles on fatigue and fracture properties of two-phase epoxy polymers reinforced with different weight percentages of GNPs.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that at higher energy release-rates, the CNFs played a larger role at resisting the fast fatigue crack growth when compared to the GNPs. As a mechanism of improving the fatigue property of epoxy nanocomposites, Bhasin et al [ 23 ] assessed the effectiveness of electric field orientation of GNPs. The authors showed that the orientation of the GNPs caused by an electric field led to more enhancement in the fatigue crack growth resistance of the resin compared to that produced by adding randomly-aligned GNPs, especially in the near threshold region.…”
Section: Introductionmentioning
confidence: 99%